A high-speed, 240-frames - Krymski, A.I (IEEE Transactions on electron devices)
This paper describes a large-format 4-Mpixel (2352×1728) sensor with on-chip parallel 10-b analog-to-digital converters (ADCs). The chip size is 20×20 mm with a 7-μm pixel pitch. At a 66-MHz master clock rate and 3.3-V operating voltage, it achieves a high frame rate of 240 frames/s delivering 9.75 Gb/s of data with power dissipation of less than 700 mW. The principal architectural features of the sensor are discussed along with the results of sensor characterization.